PENGARUH KEBERADAAN KAMPUS UNIVERSITAS INDRAPRASTA PGRI TERHADAP PERKEMBANGAN WILAYAH KECAMATAN JAGAKARSA JAKARTA SELATAN - SOEPARDI HARRIS; ATIE ERNAWATI (LPPM, 2013)
The presence of a university in the region has always been a city embryo growth. PGRI Indraprasta University campus built in the region in 2004 Jagakarsa a magnet for growth in the sub-region in particular the Western Cape region. Her presence not only spur non-physical changes but also changes physically. Changes in non-physical visible through changes in population structure, changes in the level of job and business opportunities as well as income levels around the site Unindra Campus. It is identified with a lot of economic activity growth (multiplier effect) to serve the campus community and the population growth rate is very large in the region. Physically this is seen through changes in economic activity and changes in land use, including changes in the intensity of land use and the characteristics of the type of activities, as seen through the spatial changes. Through a survey approach, this study analyzed quantitatively and qualitatively. The quantitative study using statistical methods to analyze data on how much influence the presence unindra campus to regional growth in the Western Cape districts, while qualitatively, the data were analyzed based on the theory of a trickling down effect (impact of hatchery down). Arising from the activities, the results suggest that the development of Jagakarsa, both physical and non-physical, mostly in response to the presence of Campus Unindra in the region. This is indicated by the correlation coefficient between the Campus Unindra to the development of the region by 0748, and the coefficient of determination resulting from Campus Unindra free variable and bound variable region development by 56%. This research is expected to contribute to the Government on the use of growth and land use policies around campus Unindra. Keywords: campus, regional development, multiplier effect, District Jagakarsa.